Intrahepatic recurrence of single nodular hepatocellular carcinoma after surgical resection: an analysis by segmental distribution. Issue 12 (17th September 2018) - Kim, Jin‐Min; Lee, Seung‐Hyun; Shin, Woo Young; Lee, Keon‐Young; Kim, Jun Mee; Ahn, Seung‐Ik
Abstract : Background: Intrahepatic recurrence is the major cause of management failure after surgical resection of hepatocellular carcinoma (HCC). In the present study, we analysed intrahepatic recurrence by HCC distribution using Couinaud's liver segments. Methods: Recurrence proximity levels were defined with respect to primary tumour locations from Level LR (locoregional) to Level IV. Initial and recurrent tumours were compared with segmental distribution of their locations, and recurrence proximity levels were compared with initial tumour locations and disease‐free survival. Results: Eighty‐five (58.2%) of 146 patients with single nodular HCC experienced intrahepatic recurrence after surgical resection with a mean disease‐free survival of 20.8 ± 21.1 months. Segmental distributions of initial and recurrent tumour locations were not significantly different ( P  > 0.05), and both were similar to the normal segmental volume distribution except segments S5, S6 and S8. Recurrences in proximity levels LR to IV were 11.1%, 34.9%, 25.4%, 21.4%, and 7.1%, respectively, and this distribution agreed well with theoretical proximity level distribution ( P  > 0.05). Disease‐free survivals for different recurrence levels were not different ( P  = 0.530). Conclusion: Intrahepatic recurrences after surgical resection of single nodular HCC occurred evenly in the remnant liver, and the timing was independent of the proximity between initial and recurrent tumours. Prevention was found to be proportional to the amount of liver segments removed. Surgical plans should take this into consideration.